The Influence of Profitability, Firm Size, and Leverage on Tax Aggressiveness: Evidence from Food and Beverage Companies Listed on the Indonesia Stock Exchange (2023–2025) - Nadia Desti Agustin; Hendry Saladin; Erdiansyah (Darul Yasin Al Sys, 2026)
Tax aggressiveness remains a major concern in corporate taxation because it may reduce government revenue while reflecting firms’ strategic tax-planning practices. However, empirical evidence regarding the effects of corporate financial characteristics on tax aggressiveness remains inconclusive, particularly within Indonesia’s food and beverage subsector. This study aims to examine the effects of profitability, firm size, and leverage on tax aggressiveness among food and beverage companies listed on the Indonesia Stock Exchange during 2023–2025. A quantitative approach with an explanatory research design was employed using secondary data derived from audited annual financial statements. The sample comprised 14 companies selected through purposive sampling, and the data were analyzed using multiple linear regression with IBM SPSS. The findings indicate that profitability, firm size, and leverage have no significant effects on tax aggressiveness, either partially or simultaneously. These results suggest that corporate tax aggressiveness may be shaped by factors beyond financial performance, organizational scale, and capital structure. This study contributes recent empirical evidence to the corporate taxation literature and highlights the need to consider broader organizational, governance, and regulatory determinants when examining corporate tax behavior. The findings also provide practical implications for companies and relevant stakeholders seeking to strengthen transparent, accountable, and sustainable corporate tax governance.